Impact of trematode infections on periphyton grazing rates of freshwater snails - Vivas Muñoz, Jenny Carolina; Hilt, Sabine; Horák, Petr; Knopf, Klaus (Parasitology research, 2018)
In freshwater ecosystems, snails can significantly influence the competition between primary producers through grazing of periphyton. This activity can potentially be modified by trematodes, a large group of parasites which mostly use molluscs as the first intermediate host. Available studies, however, show contradictory effects of trematodes on snail periphyton grazing. Here, we used four different freshwater snail-trematode systems to test whether a general pattern can be detected for the impact of trematode infections on snail periphyton grazing. In our experimental systems, mass-specific periphyton grazing rates of infected snails were higher, lower, or similar to rates of non-infected conspecifics, suggesting that no general pattern exists. The variation across studied snail-trematode systems may result from differences on how the parasite uses the resources of the snail and thus affects their energy budget. Trematode infections can significantly alter the grazing rate of snails, where, depending on the system, the mass-specific grazing rate can double or halve. This underlines both, the high ecological relevance of trematodes and the need for comprehensive studies at the species level to allow an integration of these parasite-host interactions into aquatic food web concepts.
Keywords: Grazing rates; Fresh Water; Snails; perifyton; ekosystém; Periphyton; ekologie; Freshwater snails; Host–parasite interaction; Trematode Infections; sladká voda; Ecology; Eating; potravní řetězec; hlemýždi; zvířata; Host-Parasite Interactions; Food Chain; Trematoda; interakce hostitele a parazita; Trematodes; Ecosystem; přijímání potravy; infekce červy třídy Trematoda; Animals